(untitled) (International journal of artificial intelligence, 2026)
Artificial intelligence (AI) technologies have become one of the most important factors in the rapid development of electronic commerce systems. AI-based solutions are widely used in customer behavior analysis, personalized recommendation systems, automated customer service, logistics optimization, fraud detection, and demand forecasting. This article analyzes the effectiveness of artificial intelligence technologies in electronic commerce based on scientific literature, statistical data, and modern practical approaches. The study examines machine learning algorithms, recommendation systems, natural language processing technologies, and deep learning models applied in e-commerce platforms. The article also evaluates the advantages and limitations of AI technologies in improving customer satisfaction, increasing sales volume, and enhancing operational efficiency. The findings indicate that AI-based personalized recommendation systems significantly improve customer engagement and conversion rates while reducing operational costs. At the same time, issues related to data privacy, algorithmic bias, and technological infrastructure remain major challenges for the sustainable implementation of AI technologies in electronic commerce.